PHARMACEUTICO- ANALYTICAL STUDY OF RASAMANIKYA PREPARED BY VARIOUS METHODS - Kulkarni, Santosh (International Journal of Ayurveda and Pharma Research, 2019)
Rasamanikya prepared from Shodhita Haritala is one of the effective and economical medicines used in different skin and respiratory disorders. Different methods are explained in the classics for the preparation of Rasamanikya and few adopted methods are also developed from scholars of Rasashastra depending upon their experience. Present study is aimed at exploring all these methods in detail and any modifications if needed. The Patra Haritala is subjected to different Shodhana procedures in different media, the changes observed are discussed in the article. The yield of Shodhita Haritala was 92% to 96% in different Shodhana methods. Rasmanikya is prepared in six different methods. Sharava samputa method (Method III & IV) can be considered as suitable methods for pharmaceutical preparation of Rasamanikya in large quantity as there was loss of only 11% to 13% drug was noticed. Chemical analysis and X-Ray diffraction of Patra Haritala and Rasamanikya prepared from all the methods is carried as a part of standardization. In Analytical study of all the methods, 44% to 47% of Arsenic and 22 to29% of Sulphur was present in Rasamanikya. X-RD study of Haritala and Rasamanikya samples revealed that crystalline form of Haritala was changed to relatively amorphous form in Rasamanikya prepared by I, II, III and IV methods, which indicates quick and better absorption of the drug Rasamanikya on administration making it one of the economical and potent medicine. Chemically Rasamanikya can be considered as a complex compound of As2S3 and As2O5.